Determinan Financial Technology (FinTech) dan Dampaknya Terhadap Perilaku Keuangan UMKM - Rudi Laksono; Junias Robert Gultom; Iwan Setyawan (Universitas Batanghari Jambi, 2023)
The presence of financial technology (fintech) brings alternative solutions for smooth business activities with various easy access. However, the solutions offered are still not fully accessible for use by MSMEs. The low financial literacy index of the Indonesian people, including MSME players, can be reflected in the financial behaviour of MSME players who take the financial system for granted; recording business financial flows is still common and only done simply. Based on this, this article aims to analyze financial behaviour as the impact of FinTech and financial literacy, as well as the role of FinTech in mediating the influence of financial literacy on financial behaviour. To find the answer, a survey method was used by involving 200 respondents in filling out a simple randomly selected questionnaire from MSMEs in the Polugadung Small Industry Village (PIK), East Jakarta. Data were analyzed using Partial Least Square - Structural Equation Modeling. The results show that FinTech and financial literacy have a significant positive influence on financial behaviour. Financial literacy also positively influences the use of FinTech, although its contribution is very low. FinTech only acts as a partial mediator between financial literacy and financial behaviour. The contribution of this study is that efforts to increase the use of FinTech in encouraging the progress of MSME players still need to be improved by the low financial literacy of MSME players, so intensive and massive efforts are needed to provide financial literacy education and training.